Question and Answers Forum

All Questions      Topic List

None Questions

Previous in All Question      Next in All Question      

Previous in None      Next in None      

Question Number 35933 by mondodotto@gmail.com last updated on 26/May/18

differentiate from  the first principle  y=(1/(√x))

differentiatefromthefirstprincipley=1x

Answered by ajfour last updated on 26/May/18

dy=(1/(√(x+dx)))−(1/(√x))      =(((√x)−(√(x+dx)))/((√x)(√(x+dx)))) = (((√(x[))1−(1+(dx/(2x)))])/(∣x∣))   (dy/dx) = −(1/(2x(√x))) .

dy=1x+dx1x=xx+dxxx+dx=x[1(1+dx2x)]xdydx=12xx.

Terms of Service

Privacy Policy

Contact: info@tinkutara.com